1985
DOI: 10.1080/09553008514551381
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Termination ofin VitroDNA Synthesis on Psoralen Phototreated Single-stranded Templates

Abstract: Single-stranded DNA has been photochemically induced to react with 4'-hydroxymethyl-4,5',8-trimethylpsoralen (HMT) and used as substrate for DNA replication with E. coli DNA polymerase I large fragment. By using the dideoxy sequencing procedure, it is possible to map the termination sites on the template photoreacted with HMT. These sites occur at the nucleotides preceding each thymine residue (and a few cytosine residues), emphasizing the fact that in a single-stranded stretch of DNA, HMT reacts with each thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Binding to single strands occurs to a much smaller extent,17 with no preference for the sequence surrounding the reactive thymine 18. Several studies agree that the 5’-TA site is more reactive than the 5’-AT site,11,15,16,19-24 and that repeated T-A sequences are hot spots for reaction due to the increased number of potential binding sites 15,24-26…”
Section: Introductionmentioning
confidence: 99%
“…Binding to single strands occurs to a much smaller extent,17 with no preference for the sequence surrounding the reactive thymine 18. Several studies agree that the 5’-TA site is more reactive than the 5’-AT site,11,15,16,19-24 and that repeated T-A sequences are hot spots for reaction due to the increased number of potential binding sites 15,24-26…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that psoralen interstrand diadducts block replication by E. coli DNA polymerase I, whereas psoralen monoadducts act as kinetic attenuators when located on the template strand and have no effect when located on the nick translated strand (26)(27). However, psoralen monoadducts on a single-stranded DNA template terninate DNA synthesis by E. coli DNA polymerase I large fragment, T4 DNA polymerase, and AMV reverse transcriptase (28).…”
mentioning
confidence: 99%
“…(11,12) found that UvrABC makes a dual incision only on the strand that interacts with the furan moiety of psoralen and does not cause a DSB. Moreover, while Pitte and Hearst (33) found that a dT-psoralen-dT ICL causes a 46.5° kink, Rink et al . (16) found that both MC-mono-dG and ICL dG-MC-dG lesions do not cause DNA bending.…”
Section: Discussionmentioning
confidence: 99%